THE INFLUENCE OF BANKING AND TOP MANAGEMENT SUPPORT ON CUSTOMER LOYALTY THROUGH GREEN SUSTAINABILITY AS MODERATING VARIABLE: A SYSTEMATIC LITERATUR REVIEW - Nabila Maharani; Muhammad Iqbal Fassa; Femei Purnamasari; Hanif .; Moh Mukri (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2026)
The increasing global demand for sustainable business practices is driving banking institutions to rethink how they build and maintain relationships with customers. This study was designed to examine the extent to which Green Banking Initiatives and Top Management Support contribute to the formation of Customer Loyalty, by positioning Green Sustainability as a moderating variable. Using a Systematic Literature Review (SLR) approach, 35 reputable international journals published between 2019 and 2026 were systematically reviewed to understand how green banking strategies have evolved and how they shape customer behavior. Research findings indicate that Green Banking Initiatives—including green product development, digitalization of banking services, and transparency in environmental reporting—have been proven to strengthen customer trust and foster sustainable loyalty. Meanwhile, Top Management Support has been identified as a key determinant in driving organizational change: without concrete commitment from top leadership, green initiatives often remain mere policy statements that are not grounded in daily operational practices. Green Sustainability, as a moderating variable, has been shown to play a significant role, either strengthening or weakening the link between green banking initiatives and customer loyalty, depending on how seriously an institution internalizes environmental commitments into its business governance. Based on these findings, this study encourages banking practitioners to integrate sustainability values ​​comprehensively into product design and service approaches, while also proposing to regulators to immediately formulate uniform green banking metric standards to support more objective and measurable performance evaluations. Keywords : Green Banking Initiatives, Top Management Support, Customer Loyalty, Green Sustainability, Systematic Literature Review.